Peningkatan Kualitas Tanah Menggunakan Kompos Berbasis Limbah Domestik Melalui Mesin Pencacah Sampah di Desa Gunungsari - Kaisar Khan; Fitri Liana Dewi Dewi; Sabiila Yassarhah; Sudiyono Sudiyono; Prasetyo Budi Supratno (Universitas Negeri Semarang, 2026)
The decline in soil quality due to excessive use of chemical fertilizers presents a significant challenge for farmers in Gunungsari Village, Windusari District, Magelang Regency. This situation prompted the implementation of a community service program aimed at introducing the use of compost made from domestic waste as a sustainable solution to improve soil quality and reduce dependence on chemical fertilizers. The program included training and mentoring in the use of an organic waste shredder (APO Machine) and compost making, utilizing hands-on practice, Q&A sessions, and group discussions. The results indicate improved understanding and skills among the community in managing organic waste, operating the APO machine, and using compost as an alternative to chemical fertilizers. The community's awareness of the importance of organic waste management and compost utilization has also increased, which could potentially support more sustainable farming practices in the future.